Compact 2-D FDTD Method Combined With Pad Approximation Transform for Leaky Mode Analysis - DONEGAN, JOHN; BYRNE, DIARMUID; GUO, WEI-HUA; LU, QIAOYIN (My University, 2010)
Leaky mode analysis has been carried out based on the compact 2-D finite-difference time-domain (FDTD) method combined with the uniaxial anisotropic perfectly matched-layer (UPML) absorption boundary condition and the Pade approximation transform technique. The imaginary part of the effective index of these leaky modes can be calculated independent of the real part, so very small leaky loss can be calculated reliably based on the proposed scheme. Mode coupling effects have also been accounted for naturally within the scheme because the simulation is carried out in the time domain and is full-vectorial. Leaky modes in the ARROW waveguide and the deep ridge waveguide have been analyzed by the proposed scheme. Leakage cancellation behavior for high-order leaky modes in very deeply etched ridge waveguides at specific ridge widths has been observed.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; PERFECTLY MATCHED LAYER; Nanoscience & Materials